Kajian Hukum Perdata Tentang Pertanggungjawaban Perseroan Terbatas Sebagai Subyek Hukum - Siti Nurjanah; Antony Antony (Fakultas Hukum, Universitas Internasional Batam, 2015)
Currently the corporation 's role in society is increasing and so wide. More and more corporations are emerging in Indonesia, did not rule out more frequent occurrence of criminal acts of the limited liability company. Limited liability company activities often make unfair business practices may cause harm to the state and individuals as consumers and in some cases can be categorized as a criminal offense. Ensnare the limited liability company for its actions against the law as perperators of a crime or offense is not easy. It caused of principles of criminal responsibility are traditionally built with the idea of individualism which means that individuals who may commit crimes instead of limited liabilty company.Methodology used in this research is the normative legal research. The data used in this study is a secondary data obtained from literature (library research). Once all the data is collected, then processed and analyzed to find the legal issues that are the object of study and concluded, then described descriptively. These results indicate that a limited liability company can be sued civilly through existing mechanisms.